Use of Cartesius Method on Google Maps Api to Recommend Search for Batik Crafts and Andid-Based Crafts (Case Study of Bangkalan District) - Doni Abdul Fatah (Universitas Trunojoyo Madura, 2019)
ASmart City increasingly rife discussed in order to be a solution in solving problems arising from the dynamics of an increasingly advanced and modern city. The purpose of applying the concept of smart city to increase the sense of security and comfort for its citizens, making the city more effective and efficient. Madura is an island located north of Java island. The island is dubbed Salt island “Pulau Garam” is quite well known in the field of bull race and batik handicrafts, especially in Bangkalan regency. Bangkalan regency is a developing city to realize the concept of smart city. One way that can be done is to take advantage of the market needs of batik lovers by providing easy access to the location. Utilizing google maps location search technology with Cartesian method on smartphone electronic devices, consumers will be easier in terms of information search and location of batik craftsmen scattered throughout the district of Bangkalan.